Vascular Lesions on the Left Upper Gingiva in a Patient With Port‐Wine Stains - Tinglan Yang; Mengmeng Song; Qing Liu; Zhenlai Zhu (Clinical Case Reports)
ABSTRACT Port‐wine stain patients may develop asymptomatic intraoral capillary hemangiomas ipsilateral to facial lesions. Multidisciplinary management is critical to differentiating these from neoplasms, mitigating bleeding risks, and optimizing therapies like photodynamic treatment. Regular oral monitoring is advised to detect vascular proliferation and dental abnormalities.